Three essays on international trade - Lin, Yih-ming (ProQuest Dissertations & Theses, 2005)
This dissertation contains three essays. In the first essay, we consider nontraded goods as an important impact on bilateral trade flows. A testable gravity equation is derived and a simple example is demonstrated. A sample of 1995 including 118 countries is examined. The results show that evidence from the data is consistent with the prediction of this model. In the second essay, we study a North/South model of intellectual property rights protection in which markets are not completely segmented and investigate how arbitrage affects IPRs protection. The results show that the North will not have an incentive to completely eliminate arbitrage after patents expire in the South, even when enforcement is costless. The results also show that, if the demand function is linear, there exists a pure-strategy Nash equilibrium. Furthermore, we demonstrate that the uniform universal standard for IPRs protection will never achieve global Pareto efficiency when the markets are not perfectly segmented. In the third essay, we propose a two-country model of parallel trade with innovation. This model tries to explain why some countries, such as the U.S., do not allow parallel trade and some, such as Japan, do. We find that the welfare effects of parallel trade are related to the elasticity of innovation. If the elasticity of innovation is high, the welfare of the importing country could decrease.